ПОЛИТИЧКА ОРГАНИЗАЦИЈА- ИЗВОР НА НАЦИОНАЛНО ЗНАМЕ НА ДРЖАВИТЕ ВО АФРИКА- POLITICAL ORGANIZATIONS – A SOURCE OF THE NATIONAL FLAG OF COUNTRIES IN AFRICA - Stojanoski, Nikola (Македонски хералд - Macedonian Herald, 2020)
From vexillological point of view, the African states and their national flags are quite diverse and unique in their design, as well as in their historical development. This review’s goal is to examine the national flags of those independent African states that have a direct or indirect origin in the flag of a political party which is or has been dominant in the country during the period of gaining independence, and following it.In Africa today 14 national flags have a direct connection to, or direct origin in, a flag of a political party that operates or has operated in the country. Some of these countries even today are often qualified as dominant-party political systems, where the party’s flag was the inspiration for the national flag. Regarding the rest of the flags that are subject to this review, even though the countries are considered multiparty systems, their national flags are still directly connected to a political organization that has an influential role in the political and public life of the country.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">